2008
DOI: 10.1002/ejoc.200701034
|View full text |Cite
|
Sign up to set email alerts
|

Recoverable Phase‐Transfer Catalysts with Fluorinated Anions: Generation and Reactions of Dichlorocarbene and CCl3 Anion in the Heterogeneous System KOH(s)/CHCl3/nBu4NPF6

Abstract: Tetraalkylammonium salts bearing PF6– and BF4– anions have been recognized as recoverable phase‐transfer catalysts for the synthesis of 1,1‐dichlorocyclopropane and α‐(trichloromethyl)carbinol derivatives from alkenes or aldehydes in the heterogeneous system KOH(s)/CHCl3. The catalysts retained their catalytic activity over several reactioncycles.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The unusual upfield shift of the urea protons when [Eumim]-OAc interacted with the halides promoted further investigation It has been reported that the charge densities on the F atoms of BF 4 -and PF 6 -are relative low and they only form weak hydrogen bonds with hydrogen bonding receptors [28]. Furthermore, BPh 4 -does not have an electronegative atom for hydrogen bonding with the receptor.…”
Section: Complex Anion Binding Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The unusual upfield shift of the urea protons when [Eumim]-OAc interacted with the halides promoted further investigation It has been reported that the charge densities on the F atoms of BF 4 -and PF 6 -are relative low and they only form weak hydrogen bonds with hydrogen bonding receptors [28]. Furthermore, BPh 4 -does not have an electronegative atom for hydrogen bonding with the receptor.…”
Section: Complex Anion Binding Studiesmentioning
confidence: 99%
“…Furthermore, BPh 4 -does not have an electronegative atom for hydrogen bonding with the receptor. Therefore, both the charge density properties of BF 4 -, PF 6 -and BPh 4 -and the upfield shifts of the urea protons of the ionic liquids indicate that the dominate interaction between the anions and ionic liquid receptors is not hydrogen bonding.…”
Section: Complex Anion Binding Studiesmentioning
confidence: 99%
See 3 more Smart Citations